[en] THEORETICAL EXPERIMENTAL THE FLEXURAL STUDY ON THE CONCRETE SLABS REINFORCED WITH PERMANENTS SHUTTER BAMBOO - EDUARDO HUMBERTO ACHA NAVARRO (MAXWELL, 2002)
[pt] Este trabalho tem por objetivo estudar o comportamento de lajes de concreto com fôrma permanente de bambu - LCFP - simplesmente apoiadas e submetidas à flexão. Estas lajes têm um vão de 350cm, alturas entre 11cm a 13cm e larguras de 60cm a 71cm que dependem do diâmetro dos bambus utilizados. Foram consideradas duas espécies de bambu disponíveis, Dendrocalamus giganteus e Guadua angustifolhia. Nas - LCFP - os conectores tem uma função importante. Neste estudo utilizaram-se dois tipos de conectores os quais consideram meio e diafragma inteiro do colmo de bambu. Com o objetivo de impermeabilizar o bambu e aumentar aderência entre os materiais foi utilizado o produto SIKADUR-32 GEL.Para estabelecer a eficiência dos conectores e do tratamento, realizaram-se ensaios PUSH-OUT. Com os resultados, estes foram caracterizados como flexíveis. Os ensaios de flexão foram levados a cabo até as cargas de colapso. Pela instrumentação das três lajes foram registrados e analisados os diagramas dos principais parâmetros. Os resultados foram comparados com os obtidos teoricamente. Nas análises foram estudadas as cargas criticas e as de serviço com base em critérios e metodologias recomendadas. Finalmente algumas variáveis são determinadas para estudos futuros. === [en] The main objective of this thesis is to study the behavior of bamboo permanent shutter concrete slab BPSCS subjected to four points bending test. The boundary conditions of the slabs are simply supported and have 350cm free spans, with the height between 11cm to 13cm and the widths of 60cm to 71cm respectively depending on the diameter of bamboo used. Two most commonly available bamboo species Dendrocalamus giganteus and Guadua angustifolhia are considered. In the BPSCS the connectors have an important function. In this study two types of connectors considering half and the entire diaphragm of the whole bamboo culm was used. To improve bonding between bamboo and concrete in addition to create an impermeable surface of the bamboo SIKADUR-32 GEL was applied.To establish the efficiency of the connectors and the considered treatment PUSH-OUT tests were carried out. The test results proved that both types of the connectors are flexible. The tests were carried out up to the failure loads. Through the instrumentation of the three tested slabs the load deflections, stress- strain curves of the slabs at different points were registered and analyzed. The results in turn were compared with those obtained theoretically. In the analyses both resistance and serviceability criteria were studied. Based on the findings preliminary design methods are recommended. Finally the variables to be studied in future are given.